The effectiveness of commercially available sports drinks - Coombes, J. S.; Hamilton, K. L. (Sports Medicine, 2000)
The purpose of this review is to evaluate the effectiveness of commercially available sports drinks by answering the questions: (i) will consuming a sports drink be beneficial to performance? and (ii) do different sports drinks vary in their effectiveness? To answer these questions we have considered the composition of commercially available sports drinks, examined the rationale for using them, and critically reviewed the vast number of studies that have investigated the effectiveness of sports drinks on performance. The focus is on the drinks that contain low carbohydrate concentrations (<10%) and are marketed for general consumption before and during exercise rather than those with carbohydrate concentrations >10%, which are intended for carbohydrate loading. Our conclusions are 3-fold. First, because of variations in drink composition and research design, much of the sports drinks research from the past cannot be applied directly to the effectiveness of currently available sports drinks. Secondly, in studies where a practical protocol has been used along with a currently available sports beverage, there is evidence to suggest that consuming a sports drinks will improve performance compared with consuming a placebo beverage. Finally, there is little evidence that any one sports drink is superior to any of the other beverages on the market.